Social media knowledge sharing and academic performance in Malaysian higher education institutions - Umi Nabila, Alias; Muhammad Ashraf, Fauzi (Universiti Kebangsaan Malaysia, 2025)
In the sociocultural dimension of the borderless age of technology, individuals are jumping on the bandwagon, where associations in modern society transpire through social media. Social media platforms offer communication, interaction and knowledge sharing as well as diverse other advantages that contribute to their influence on users, especially students. Research on the effectiveness of social media as an information-sharing tool has still not been widely adopted. Therefore, this study explores how social media contributes to students' perceptions of academic performance in public higher education institutions (HEIs) in Malaysia. This study received 411 responses from students in 20 public higher education institutions in Malaysia. This study uses partial least squares structural equation modelling (PLS-SEM). Fornell & Larcker criteria and heterotrait-monotrait correlation ratio (HTMT), both indicators of cross-loading, were used to assess discriminant validity. This study revealed that social interaction ties and identification significantly affect knowledge sharing and knowledge sharing in turn positively affects perceived academic performance. Thus, this supports the idea that knowledge sharing can improve academic performance. This research provides essential insight into enhancing academic learning in Malaysia by fostering positive relationship factors and encouraging knowledge sharing behaviours. Furthermore, provides a valuable perspective on how student relationships and knowledge sharing practices can improve educational outcomes in Malaysia.